Animated Video for Increasing Primary School Teachers’ Knowledge Regarding First Aid Management of Dental Avulsion - Katthika, Vassa Khema; Fauziah, Eva; Budiardjo, Sarworini Bagio (Brazilian Dental Science, 2020)
Introduction: Dental avulsion is a condition in which the tooth is completely dislodged from its socket. Inappropriate management when trauma occurs can complicate the prognosis of the tooth. The majority of injuries to children's teeth occur in the school environment and teachers play an essential role in providing first aid at the accident site. However, the school teacher’s knowledge regarding first aid dental avulsion is inadequate. Objectives: The purpose of this study was to analyze the effect of an animated video (First Aid Management of Dental Avulsion) on the knowledge of primary school teachers. Materials and methods: This clinical experimental study comprised 54 teachers from 13 public elementary schools in Central Jakarta who were chosen randomly to fill out a questionnaire before and after watching the animated video. Results: Data analysis using the Wilcoxon comparative test showed that there was a statistically significant increase (P